A comparative study using thrombin generation and three different INR methods in patients on Vitamin K antagonist treatment. (12th May 2017) - Riva, N.; Vella, K.; Meli, S.; Hickey, K.; Zammit, D.; Calamatta, C.; Makris, M.; Kitchen, S.; Ageno, W.; Gatt, A.
Summary: Introduction: Vitamin K antagonist (VKA) treatment requires routine monitoring using the international normalized ratio (INR). However, different INR assays may vary in their results. The aim of this study was to assess the agreement of three different INR methods, compared with thrombin generation, in patients on VKA treatment. Methods: Sixty patients attending the Anticoagulation Clinic at Mater Dei Hospital (Msida, Malta) for VKA monitoring between August and September 2015 were enrolled. The INR was tested using a point‐of‐care (POC) device (CoaguChek XS Plus, Roche Diagnostics) for both capillary and venous blood samples, a photo‐optical (Sysmex CS‐2100i/CA‐1500, Siemens) and a mechanical clot detection system (Thrombolyzer XRC, Behnk Elektronik). All assays used human recombinant thromboplastin as reagent. Thrombin generation was performed using the calibrated automated thrombogram. Results: There was a negative curvilinear correlation between the endogenous thrombin potential and different INR assays ( r ≤−.75) and a strong positive linear correlation between the CoaguChek XS Plus on capillary samples and the other INR methodologies ( r ≥.96). Conclusion: All different INR assays showed good correlation with the thrombin generation potential. The POC INR showed one of the highest correlation coefficients with thrombin generation, confirming the POC devices as an accurate, valid alternative to laboratory INR in VKA patients.